Effects of dexamethasone on early cognitive decline after cardiac surgery: A randomised controlled trial. Issue 11 (November 2017) - Glumac, Sandro; Kardum, Goran; Sodic, Lidija; Supe-Domic, Daniela; Karanovic, Nenad
Abstract : BACKGROUND: Postoperative cognitive decline (POCD), a very common complication after cardiac surgery, is characterised by impairment of both memory function and intellectual ability as well as being associated with increased use of healthcare resources. The investigators focused on the role of the inflammatory response to a surgical procedure as a potential factor involved in the pathogenesis of POCD. OBJECTIVE: The use of prophylactic dexamethasone to attenuate the inflammatory response was hypothesised to reduce the risk of POCD. DESIGN: Randomised controlled study. SETTING: Single university teaching hospital, from March 2015 to January 2016. PATIENTS: A total of 169 patients scheduled for elective cardiac surgery were enrolled, and 161 patients were included in the analyses. INTERVENTION: Patients were randomised to receive a single intravenous bolus of 0.1 mg kg −1 dexamethasone ( n = 85) or placebo ( n = 84) 10 h before the surgery. MAIN OUTCOME MEASURES: The primary outcome measure in both groups was the incidence of POCD on the 6th day after surgery. The investigators also evaluated the effect of dexamethasone on the incidence of systemic inflammatory response syndrome, postoperative C-reactive protein levels and postoperative serum S100β protein levels. RESULTS: Compared to the placebo group, the dexamethasone group showed statistically significant reductions in the incidence of POCD (relative risk, 0.43; 95% confidence interval, 0.21 to 0.89; P = 0.02), the incidence of systemic inflammatory response syndrome (30.0 versus 58.0%, P < 0.001) and postoperative C-reactive protein levels ( P < 0.001). Postoperative S100β levels were insignificantly lower ( P = 0.56) in the dexamethasone group. CONCLUSION: Preoperative administration of dexamethasone reduced the inflammatory response and thereby decreased the risk of early POCD after cardiac surgery. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT02767713. Abstract : Supplemental Digital Content is available in the text